A Retrospective Evaluation of Morbidity Pattern and Outcome of Patients Admitted in Paediatric Intensive Care Unit in a Tertiary Care Rural Teaching Hospital - A. Ambike, Deepali; Bhavari, Vijay L. (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Background: The care of severely unwell children continues to be one of the most demanding and difficult elements of paediatrics. The primary goal of the Paediatric Intensive Care Unit is to avoid death by closely monitoring and treating severely ill children who are at high risk of dying. There is a scarcity of data on paediatric critical care in developing countries. The efficacy of treatment can be determined by evaluating the outcomes of medical interventions. This aids in better decision making, improving care quality, and, if necessary, changing management's future direction. This study will also aid in the investigation of the causes of morbidity and mortality among children in our hospital. The study's goals and objectives are to evaluate the morbidity pattern and outcomes of admissions in the PICU of a rural teaching hospital, as well as to take measures to prevent morbidity and mortality by improving critical care facilities. Methods: This was a retrospective study of cases admitted to our teaching hospital's paediatric ICU in the last two and a half years, taking into account the estimated sample size. Data will be gathered from the PICU and the Medical Records Department. The medical record will be used to study the details, which will then be analysed and interpreted based on the medical record details. Results: A total of 417 patients were admitted to our PICU over the course of the study's 30 months. Of the total cases studied, Maximum i.e. 180(43.2%) had age below 1 year. The minimum – maximum range of age was between 1 day to 18 years. About 228(54.7%) cases were males and 189(45.3%) were females. LRTI was the most common diagnosis, accounting for 61 (14.7%) of cases. The respiratory system was the most frequently involved system, accounting for 101 (21.8%) of all cases. 357 (85.6 %) of the total cases studied were discharged, 36 (8.6 percent) had DAMA (discharge against medical advice), and 24 (5.8%) expired. Conclusions: Mortality was low in our PICU. Based on the findings of this study, we conclude that in our rural PICU, with better treatment protocols and skilled expertise/Pediatric Intensivist, we have a better chance of facilitating the care of critically ill patients and achieving a favourable outcome.